Biomechanics of tendrils and adhesive pads of the climbing passion flower Passiflora discophora. (21st October 2021) - Klimm, Frederike; Schmier, Stefanie; Bohn, Holger F; Kleiser, Svenja; Thielen, Marc; Speck, Thomas
Abstract: The climbing passion flower Passiflora discophora features branched tendrils with multiple adhesive pads at their tips allowing it to attach to large-diameter supports and to flat surfaces. We conducted tensile tests to quantify the performance of this attachment system. We found that the force at failure varies with substrate, ontogenetic state (turgescent or senescent), and tendril size (i.e. tendril cross-sectional area and pad area). The tendrils proved to be well balanced in size and to attach firmly to a variety of substrates (force at failure up to 2N). Pull-off tests performed with tendrils grown on either epoxy, plywood, or beech bark revealed that senescent tendrils could still bear 24, 64, or 100% of the force measured for turgescent tendrils, respectively, thus providing long-lasting attachment at minimal physiological costs. The tendril main axis was typically the weakest part of the adhesive system, whereas the pad–substrate interface never failed. This suggests that the plants use the slight oversizing of adhesive pads as a strategy to cope with 'unpredictable' substrates. The pads, together with the spring-like main axis, which can, as shown, dissipate a large amount of energy when straightened, thus constitute a fail-safe attachment system. Abstract : Energy-dissipating tendrils of the climbing plant Passiflora discophora feature multiple adhesive pads that provide secure and long-lasting attachment to a variety of substrates.